2018
DOI: 10.1051/0004-6361/201833055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metallicity and star formation rate on the time-dependent, galaxy-wide stellar initial mass function

Abstract: The stellar initial mass function (IMF) is commonly assumed to be an invariant probability density distribution function of initial stellar masses. These initial stellar masses are generally represented by the canonical IMF, which is defined as the result of one star formation event in an embedded cluster. As a consequence, the galaxy-wide IMF (gwIMF) should also be invariant and of the same form as the canonical IMF; gwIMF is defined as the sum of the IMFs of all star-forming regions in which embedded cluster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
201
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 146 publications
(209 citation statements)
references
References 151 publications
(201 reference statements)
8
201
0
Order By: Relevance
“…To combine the two methods, one needs to convert one metallicity measure to the other, which is not a straightforward procedure. However, we note that the metallicity dependence of the IMF has only a secondary effect on the correction factors calculated by Jeřábková et al (2018) and so the exact form of the relation does not have a strong effect on our results. For the purpose of this study we assume an example relation between [O/H] and [Fe/H] as shown in Fig.…”
Section: Sfr Corrections For the Non-universal Imfmentioning
confidence: 54%
See 4 more Smart Citations
“…To combine the two methods, one needs to convert one metallicity measure to the other, which is not a straightforward procedure. However, we note that the metallicity dependence of the IMF has only a secondary effect on the correction factors calculated by Jeřábková et al (2018) and so the exact form of the relation does not have a strong effect on our results. For the purpose of this study we assume an example relation between [O/H] and [Fe/H] as shown in Fig.…”
Section: Sfr Corrections For the Non-universal Imfmentioning
confidence: 54%
“…Such corrections to the Kennicutt (1998) relation were recently calculated by Jeřábková et al (2018). Using the PyPegase python wrapper 4 , Jeřábková et al (2018) combined the GalIMF code (Yan et al 2017(Yan et al , 2019a which computes the galaxy-wide IMF(S FR, [Fe/H]) with PEGASE.2 stellar population synthesis code (Fioc & Rocca-Volmerange 1999;Fioc et al 2011) to produce the Hα flux for a given stellar population assuming a constant star formation history (SFH). For the purpose of this paper we extended previous calculations for a larger parameter space of SFRs (10 −5 M /yr, 10 3 M /yr) and [Fe/H] metallicities (-5,1).…”
Section: Sfr Corrections For the Non-universal Imfmentioning
confidence: 85%
See 3 more Smart Citations